HELLP-SYNDROME - A. D. Makatsariya; V. O. Bitsadze; D. Kh. Khizroeva (IRBIS LLC, 2016)
The pathophysiology of HELLP syndrome is not well defined. Nowadays endothelial dysfunction if considered the key moment of the development of HELLP-syndrome. Endothelial cell dysfunction results in hypertension, proteinuria, and increased platelet activation and aggregation. Furthermore, activation of the coagulation cascade causes consumption of platelets due to adhesion onto a damaged and activated endothelium, in addition to microangiopathic hemolysis caused by shearing of erythrocytes as they traverse through capillaries laden with platelet-fibrin deposits. Multiorgan microvascular injury and hepatic necrosis causing liver dysfunction contribute to the development of HELLP.